All-Star 1 Student Book + CD - Sherman Kristin (MC Graw Hill, 2005)
All-Star is a four-level, standards-based series for adult English learners featuring a picture-dictionary approach to vocabulary building. Big picture scenes in each unit provide springboards to a wealth of activities that develop all the language skills.